CAPRi technical workshop on Watershed Management Institutions: a summary paper - Knox, Anna; Gupta, Subodh (International Food Policy Research Institute, 2000)
The System-wide Program for Collective Action and Property Rights (CAPRi) sponsored a workshop on Watershed Management Institutions, March 13-16, 1999 in Managua, Nicaragua. The workshop focused on methodologies for undertaking research on watersheds, particularly those issues and tools that enable a more thorough understanding of the complex interactions between the biophysical factors and socioeconomic institutions of watersheds. Both social and biophysical scientists from CGIAR and other research institutions were brought together to present research and participate in focused discussions on methodologies for addressing collective action and property rights, scale, participation, and impact assessment. The forum also provided an opportunity for participants to visit and learn from a watershed project being implemented by the International Center for Tropical Agriculture (CIAT), and to discuss one another's ongoing watershed research project experience and explore opportunities for collaboration.